2011
DOI: 10.2967/jnumed.111.088005
|View full text |Cite
|
Sign up to set email alerts
|

Small-Animal PET Study of Adenosine A1 Receptors in Rat Brain: Blocking Receptors and Raising Extracellular Adenosine

Abstract: Activation of adenosine A 1 receptors (A 1 R) in the brain causes sedation, reduces anxiety, inhibits seizures, and promotes neuroprotection. Cerebral A 1 R can be visualized using 8-dicyclopropylmethyl-1-11 C-methyl-3-propyl-xanthine ( 11 C-MPDX) and PET. This study aims to test whether 11 C-MPDX can be used for quantitative studies of cerebral A 1 R in rodents. Methods: 11 C-MPDX was injected (intravenously) into isoflurane-anesthetized male Wistar rats (300 g). A dynamic scan of the central nervous system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
5
24
0
Order By: Relevance
“…Unfortunately, the 0.3 mg/kg DPCPX dose completely suppressed the antidepressant-like effect of CHA. A more complete understanding of CHA and DPCPX pharmacological potency that was available after the jpet.aspetjournals.org present studies (Collins et al, 2010;Paul et al, 2011) were conducted suggests that the 0.3 mg/kg DPCPX dose results in maximal effects at blocking adenosine A 1 receptors. Furthermore, similar antidepressant-like effects of CHA alone were observed in this experiment both times the agonist was administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the 0.3 mg/kg DPCPX dose completely suppressed the antidepressant-like effect of CHA. A more complete understanding of CHA and DPCPX pharmacological potency that was available after the jpet.aspetjournals.org present studies (Collins et al, 2010;Paul et al, 2011) were conducted suggests that the 0.3 mg/kg DPCPX dose results in maximal effects at blocking adenosine A 1 receptors. Furthermore, similar antidepressant-like effects of CHA alone were observed in this experiment both times the agonist was administered.…”
Section: Discussionmentioning
confidence: 99%
“…First, complete displacement of the binding for a different adenosine A 1 receptor radiotracer was obtained with a 1 mg/kg i.p. dose of DPCPX (Paul et al, 2011). Second, CHA and DPCPX (each 0.03-0.30 mg/kg doses) altered locomotor activity through a specific interaction with brain adenosine A 1 receptors (Marston et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported that 11 C-MPDX and small-animal PET can be used to quantify regional A 1 R densities in the rodent brain (7). PET offers unique opportunities for measuring the fraction of receptor populations occupied by nonradioactive drugs in the living brain and relating levels of occupancy to the magnitude of the therapeutic effect or to unwanted side effects.…”
mentioning
confidence: 99%
“…Only a single PET study has examined changes of A 1 R expression after acute exposure of animals to ethanol [126]. In that study, Wistar rats were treated with a combination of ethanol and the AK inhibitor ABT-702, and scanned with the A 1 R ligand [ 11 C]MPDX.…”
Section: Effects Of Ethanolmentioning
confidence: 99%
“…A microPET study from our own group has indicated that A 1 R in rat brain are almost completely occupied after administration of DPCPX (3 mg/kg, i.p. ), 20 min before injection of 11 C-MPDX [126].…”
Section: A 1 R (Ant)agonistsmentioning
confidence: 99%